THE PROCESS OF CONCEPTUALIZATION IN SOLVING GEOMETRIC-FUNCTION PROBLEMS - Masta Hutajulu; Krisna Satrio Perbowo; Fiki Alghadari; Eva Dwi Minarti; Wahyu Hidayat (Jurnal Infinity, 2022)
Functional analysis has been of interest and the thinking of students should be prepared. Â Analyzing the process of conceptualizing geometric function problem solving based on the dimensions of cognitive processes and knowledge was the purpose of this study. The subjects of this study were three students selected purposively from one of the secondary schools in Indonesia. Exploration of these studies with constant comparative techniques. The results of the data analysis show that the cognitive processes that operate and the knowledge applied by students focus on the conceptualization of algebraic representations. Based on the conceptualization process, students' conceptual systems are still fragmented because of the problem of the relationship between the concept and the basis of its relationship. As a result, procedural knowledge is more dominant.